PENGARUH MURABAHAH DAN STRUKTUR MODAL SENDIRI TERHADAP IMBAL HASIL STUDI PADA BPR SYARIAH DI PULAU JAWA - Rinto Noviantoro; Umar Purwoko (UNIVED Press, 2017)
Rinto Noviantoro, Umar Purwoko; This research was aimed to determine the effect of growth and equity financing murabahah about returns in the form of return on assets in the Bank's Credit Rakyar Sharia (SRB) in the island of Java in the period quartalan ie Balance Sheet reporting period March 2011 s / d in December 2012 were published. The hypothesis testing using multiple linear test that examines the effect between murabaha and growth equity capital structure as an independent variable to variable yields as dipenden. Secondary Data collection method is by using quantitative analysis. Test statistics using Classical Test assumptions. The results of this study indicate that the murabahah and equity capital structure significantly influence yield, whereby the different results that the growth murabaha significant negative effect on BPR Syariah then capital structure itself significant positive effect on the yield on Syariah BP.Key Words: Murabahah , Own Capital Structure , and yields